Schistosoma japonicum-derived peptide SJMHE1 ameliorates allergic symptoms and responses in mice with allergic rhinitis - Gao, Xuerong; Mao, Chaoming; Zheng, Tingting; Xu, Xiaowei; Luo, Xinkai; Zhang, Shan; Liu, Jiameng; Wang, Xuefeng; Chen, Xiaojun; Dong, Liyang (Frontiers in Cellular and Infection Microbiology, 2023)
Helminth derived excretory/secretory molecules have shown efficacy in the treatment of allergic asthma in mice, but their roles in allergic rhinitis (AR) are little known. In this study, we aimed to determine the intervention effect of SJMHE1, a Schistosoma japonicum derived small molecular peptide, on ovalbumin (OVA)-induced AR mice and investigate its possible mechanism. AR was induced in BALB/c mice, following which the mice were treated with phosphate-buffered saline (PBS), OVA323-339 and SJMHE1 respectively. SJMHE1 treatment improved clinical symptoms (rubbing and sneezing), suppressed infiltrates of inflammatory cells and eosinophils in nasal mucosa, modulated the production of type-2 (IL-4 and IL-13) and anti-inflammatory (IL-10) cytokines in the nasal lavage fluids (NLF), spleen, and serum. To investigate the underlying mechanism, fluorescein isothiocyanate (FITC)-labeled SJMHE1 was subcutaneously injected into AR mice, and we found that the FITC-SJMHE1 could accumulate in spleen, but not in nasal mucosa. FITC-SJMHE1 mainly bound to CD19 positive cells (B cells), and the SJMHE1 treatment significantly increased the proportion of regulatory B cells (Bregs) and B10 cells, along with the enhancement of PR domain containing protein 1 (Prdm1) protein levels. SJMHE1 may alleviate AR by upregulating Bregs, and has great potential as a new avenue for the AR treatment.